INTERMEDIATE BAND PHOTOMETRY OF THE SCORPIO CENTAURUS ASSOCIATION AND SOUTHERN BRIGHT STARS - MENDOZA, EUGENIO (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1867)
We have made photometric observations in the (33, 35, 37, 40, 45, 52, 58, 63)-system of 333 stars of the Southern Hemisphere. Approximately one third of them are located in the Scorpio-Centaurus Association region. Possibly most of them can be considered
BOL OBS TONAN TACUB
Keywords: INTERMEDIATE, PHOTOMETRY, SCORPIO CENTAURUS ASSOCIATION, SOUTHERN BRIGHT STARS; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS